Mix Method Approach of Measuring VR as a Pedagogical Tool to Enhance Experimental Learning: Motivation from Literature Survey of Previous Study. (25th March 2022) - Asad, Muhammad Mujtaba; Naz, Aisha; Churi, Prathamesh; Guerrero, Antonio José Moreno; Salameh, Anas A.
Abstract : This research has been experimented on our previous literature review. Technological advancement has prevailed in the modern era from the 20 th century. Artificial intelligence and virtual worlds have been created for rapid technological development. This paper is aimed at exploring the effect of virtual reality as a pedagogical tool for enhancing experiential learning among undergraduate students. Considering this, it was a mixed-methods study following the design of sequential exploratory–which includes qualitative followed by quantitative part. The targeted population was undergraduate students taking education programs from Public Sector Universities of Sindh. For the qualitative part, the sample of eight undergraduate students was interviewed for exploring their perceptions about virtual reality for enhancing experiential learning. The interviewed data were thematically analyzed, which revealed seven themes. For the quantitative part, emerged seven themes were used as constructs for developing the questionnaire. It was then used for quantitative data collection having excellent reliability. A sample of 80 students was taken, and data were collected by self-administration. The quantitative data were analyzed by descriptive as well as inferential statistics. Hence, the results found a statistically significant effect of virtual reality for enhancing experiential learning. However, user-friendliness ensures the applicability of virtual reality. Thus, it concluded that the implementation of virtual reality influences experiential learning enhancement. However, the implementation of virtual reality still depends upon the user-friendly nature of technology and virtual reality.